ANALISIS FILM TRILOGI CINTA SUBUH PRODUKSI DARUL QUR`AN (DAQU) MOVIE TAHUN 2014-2015 MELALUI ANALISIS SEMIOTIKA ROLAND BARTHES - Nanda Lifia Pratiwi; Tawvicky Hidayat (Bayan lin-Naas : Jurnal Dakwah Islam, 2020)
AbstractResearch this purposeful for know dakwah messages in the film Love Dawn Movie Daqu production by way of semiotic. researchers use semiotics as a tool of analysis methods. Semiotics is a technique researching and interpreting signs or text.Scene dakwah messages contained in the film Trilogy of Love Dawn. Among them : Dakwah messages that to be pertient with islamic law and ethics, denotation of meaning contained in the film Love Dawn Movie Daqu production is to visualize symbols when lift scene, Ratih to break off Angga, behave a connaction with type a rival, about love that real just to god and prophet, certainty that god`s guedance just ownership god`s, and morals to propose marriage. While meaning connotations dakwah messages to approach adultery, dakwah messages to be muslima woman dutiful, to add love to god and prophet`s, to add certainty god`s guedance just ownership god`s, and morals to propose marriage.   Key Words : Dakwah, Love Dawn, Semiotic.